2018
DOI: 10.3389/fphys.2018.01367
|View full text |Cite
|
Sign up to set email alerts
|

High-Intensity Interval Training Is Associated With Alterations in Blood Biomarkers Related to Brain Injury

Abstract: Purpose: Blood biomarkers are a useful tool to study concussion. However, their interpretation is complicated by a number of potential biological confounds, including exercise. This is particularly relevant in military and athletic settings where injury commonly occurs during physical exertion. The impact of high-intensity interval training (HIIT) on putative brain injury biomarkers remains under-examined. The purpose of this study was to observe the effects of HIIT on a panel of blood biomarkers associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 71 publications
2
34
0
Order By: Relevance
“…MCP-1 has also been studied in the context of exercise. A single bout of HIIT exercise increased circulating MCP-1 concentrations in young men 22 whereas in another study, MCP-1 concentrations did not change after two weeks of HIIT training 23 . Two weeks of moderate intensity training in obese subjects also did not change MCP-1 concentrations 24 .…”
Section: Introductionmentioning
confidence: 79%
“…MCP-1 has also been studied in the context of exercise. A single bout of HIIT exercise increased circulating MCP-1 concentrations in young men 22 whereas in another study, MCP-1 concentrations did not change after two weeks of HIIT training 23 . Two weeks of moderate intensity training in obese subjects also did not change MCP-1 concentrations 24 .…”
Section: Introductionmentioning
confidence: 79%
“…15 High intensity interval training can also lead to increased serum tau levels in the bloodstream; however, a two-week period of such training is alleged to blunt the tau release during subsequent training sessions. 16 Transient hypoxia during breath-hold diving has been associated with elevated tau levels, but a small pilot study on divers with DCS found no statistically significant elevation of tau concentration in cerebrospinal fluid (CSF). 17,18 Neurofilament light protein (NfL) is a structural axonal protein which is found mainly in myelinated subcortical axons.…”
Section: Introductionmentioning
confidence: 99%
“…As highlighted in a recent systematic review, however, much of the prior blood biomarker work in SRC has been limited to relatively small sample sizes and/or did not include preseason (ie, preinjury) assessments . Moreover, recent findings that some of the proposed biomarkers for SRC are sensitive to exercise and/or exposure to minor head impacts during sport participation without frank concussion highlight the importance of appropriate control comparisons …”
mentioning
confidence: 99%